2013
DOI: 10.1016/j.chemosphere.2012.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two swine manure treatment systems on chemical composition and on the reduction of pathogens

Abstract: Swine effluents must be correctly handled to avoid negative environmental impacts. In this study, the profiles of two swine manure treatment systems were evaluated: a solid-liquid separation step, followed by an anaerobic reactor, and an aerobic step (System 1); and a biodigester followed by serial lagoons (System 2). Both systems were described by the assessment of chemical, bacterial and viral parameters. The results showed that in System 1, there was reduction of chemicals (COD, phosphorus, total Kjeldhal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 20 publications
3
30
1
11
Order By: Relevance
“…Multiple studies have identified Salmonella, Escherichia coli (E. coli), Porcine circovirus type 2 (PCV2), and many other microorganisms in swine wastewater even after conventional biological treatment, as anaerobic digestion (Fongaro et al 2014;Viancelli et al 2013;Vanotti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have identified Salmonella, Escherichia coli (E. coli), Porcine circovirus type 2 (PCV2), and many other microorganisms in swine wastewater even after conventional biological treatment, as anaerobic digestion (Fongaro et al 2014;Viancelli et al 2013;Vanotti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens that are resistant to most alternative treatments, as E. coli and PCV2, are used as water quality indicators (Viancelli et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the fourth largest producer and exporter of pork in the world (Marçal et al, 2016), accounting for 3,360.0 Mg year -1 of global pork production (Viancelli et al, 2013). In the last decade, this production increased 38.9% (ABPA, 2016), raising concerns about the daily concentration of residues of the activity.…”
Section: Introductionmentioning
confidence: 99%
“…Swine wastewater (SW) contains urine, faeces, water, undigested food residues, antimicrobial drug residues and pathogenic microorganisms (Viancelli et al, 2013). When adequately treated, SW may have a high potential for use as fertilizers in agriculture (Kessler et al, 2013;Andrade et al, 2014;Abdoulkader et al, 2015;Egewarth et al, 2015;Homem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Swine farming is an important activity in the agribusiness (VIANCELLI et al, 2013). In the meat market it is responsible for the creation of jobs, acting as an incomestabilizing factor for thousands of families SUZUKI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%